Mitochondrial protein deacetylation by SIRT3 in osteoclasts promotes bone resorption with aging in female mice - Kimberly K. Richardson; Gareeballah Osman Adam; Wen Ling; Aaron Warren; Adriana Marques-Carvalho; Jeff D. Thostenson; Kimberly Krager; Nukhet Aykin-Burns; Stephanie D. Byrum; Maria Almeida; Ha-Neui Kim (Elsevier, 2024)
Objectives: The mitochondrial deacetylase sirtuin-3 (SIRT3) is necessary for the increased bone resorption and enhanced function of mitochondria in osteoclasts that occur with advancing age; how SIRT3 drives bone resorption remains elusive. Methods: To determine the role of SIRT3 in osteoclast mitochondria, we used mice with conditional loss of Sirt3 in osteoclast lineage and mice with germline deletion of either Sirt3 or its known target Pink1. Results: SIRT3 stimulates mitochondrial quality in osteoclasts in a PINK1-independent manner, promoting mitochondrial activity and osteoclast maturation and function, thereby contributing to bone loss in female but not male mice. Quantitative analyses of global proteomes and acetylomes revealed that deletion of Sirt3 dramatically increased acetylation of osteoclast mitochondrial proteins, particularly ATPase inhibitory factor 1 (ATPIF1), an essential protein for mitophagy. Inhibition of mitophagy via mdivi-1 recapitulated the effect of deletion of Sirt3 or Atpif1 in osteoclast formation and mitochondrial function. Conclusions: Decreasing mitophagic flux in osteoclasts may be a promising pharmacotherapeutic approach to treat osteoporosis in older adults.